Beef cattle farmers behavior toward biosecurity - Lestari, V. S.; Rahardja, D. P.; Mappigau, P.; Rohani, S .T.; Sirajuddin, S. N. (Diponegoro University, 2019)
Beef cattle are meat producers which are beneficial to humans. The purpose of this study was to identify and to control the behavior of beef cattle farmers towards biosecurity in Lamasi District - Luwu Region, South Sulawesi Province. This type of research was descriptive research. The research method was survey to participatory research and the Focus Group Discussion. Total sample was 50 respondents. Data were obtained through interview using questionnaires and observations. Data were analyzed using descriptive statistic. Likert scale 1 until 3 were used to know the response level of disagree and agree about biosecurity. The results showed that beef cattle farmers less agree to biosecurity adoption. Based on subjective norm, farmers’ behaviors agree to adopt biosecurity if they were supported by community leaders and other livestock farmers or farmer groups. Behavior control which becomes the main obstacles to implementing biosecurity are habits, prior implementation and risks. The supporting factors needed time, can be tested on a small scale cattle business, according to the needs of cattle farmers, needed workers, needed knowledge, skills, and information about biosecurity. Beef cattle farmers should be motivated to adopt biosecurity in order to get a healthy beef cattle.